Women’s Empowerment in Agri-food Systems Governance (WEAGov): A new assessment framework - Kyle, Jordan; Ragasa, Catherine (International Food Policy Research Institute, 2023)
The Women’s Empowerment in Agri-food Systems Governance framework (WEAGov) is a diagnostic, theory-based tool developed by IFPRI to help evaluate the extent to which women are empowered across the national-level policy cycle related to agri-food systems. All too often, women’s voices are missing from the agri-food policy process, even when women are disproportionately employed in the sector and disproportionately affected by shocks and climate change. WEAGov provides a way to identify gaps and opportunities to raise women’s voice and agency at different stages of the policy cycle, as well as a basis for monitoring progress in women’s empowerment in agri-food systems governance within and across countries over time. The assessment framework proposes 17 operational indicators to identify women’s consideration, inclusion and influence across different stages of the policy process. We introduce rapid assessment tools to measure these 17 indicators through a variety of sources. Empirical application of the assessment tool in Nigeria relied on surveys with 250 purposively sampled agri-food systems experts; surveys with 140 different organizations involved in the agri-food systems policy process across federal and state agri-food systems ministries, independent agencies, civil society organizations and private-sector entities; and a validation workshop with local experts. In a time when donors, research communities and policymakers are increasingly focused on women’s empowerment, WEAGov offers a practical framework through which practitioners and researchers can assess when and where opportunities may exist to enhance women’s voice in the policy decisions that shape their lives and livelihoods.